Trends in regional development in Slovenia in the light of the goals of sustainable development - MALLY, Katja Vintar (European Journal of Geography, 2022)
Applying sustainable development into practice is an important national and regional policy goal in Slovenia; in addition, the country’s membership in the European Union further commits it to the goals of sustainable development. The research presented in this article is based on the use of a set of 32 economic, social and environmental indicators of sustainable development and the calculation of a synthetic indicator of sustainable regional development for all twelve Slovenian NUTS-3 regions in the period 2015–2019. In the final step, a synthetic assessment of the possibilities for implementing sustainable development in individual Slovenian regions is given, in which regions are classified into four different types. A comparison with the previous five-year period showed that Slovenia achieved progress in most of the socio-economic aspects of sustainable development analyzed, while the situation deteriorated with respect to environmental aspects. The largest differences among Slovenian regions were calculated in the economic area, and the smallest in the environmental area, which is also in line with the findings of previous research. There continues to be a development divide between the more prosperous western part of the country and the eastern part, which lags behind and for the most part also has poorer prospects for sustainable development. This trend is unfavorable for the balanced as well as sustainable development of Slovenian regions.